The surgical strategy and technical nuances of in situ side-to-side bypass for the management of complex intracranial aneurysms - Wang, Hua-wei; Xue, Zhe; Sun, Cai-hong; Kong, Dong-sheng; Wu, Chen; Sun, Zheng-hui (Frontiers in Neurology, 2023)
Background Despite continuous advances in microsurgical and endovascular techniques, the treatment of complex aneurysms remains challenging. Aneurysms that are dilemmatic for conventional clipping or endovascular coiling often require bypass as part of a strategy to reduce the risk of ischemic complications. In anatomically favorable sites, the intracranial–intracranial in situ bypass may be an appealing choice. This article details the surgical strategies, operative nuances, and clinical outcomes of this technique with a consecutive series in our department. Methods A retrospective review of a prospectively maintained neurosurgical patient database was performed to identify all patients treated with side-to-side in situ bypass from January 2016 to June 2022. In total, 12 consecutive patients, including 12 aneurysms, were identified and included in the series. The medical records, surgical videos, neuroimaging studies, and follow-up clinic notes were reviewed for every patient. Results Of the 12 aneurysms, there were 5 middle cerebral artery aneurysms, 4 anterior cerebral artery aneurysms, and 3 posterior inferior cerebellar artery aneurysms. The morphology of the aneurysms was fusiform in 8 patients and saccular in the remaining 4 patients. There were 3 patients presented with subarachnoid hemorrhage. The treatment modality was simple in situ bypass in 8 cases and in situ bypass combined with other modalities in 4 cases. Bypass patency was confirmed in all cases by intraoperative micro-doppler probe and (or) infrared indocyanine green (ICG) video angiography intraoperatively and with digital subtraction angiography (DSA) or computed tomography angiography (CTA) postoperatively. None of the patients developed a clinically manifested stroke due to the procedure though a callosomarginal artery was intentionally removed in one patient. The median follow-up period was 16.2 months (6-36). All patients had achieved improved or unchanged modified Rankin scale scores at the final follow-ups. Conclusion Cerebral revascularization technique remains an essential skill for the treatment of complex aneurysms. The in situ bypass is one of the most effective techniques to revascularize efferent territory when vital artery sacrifice or occlusion is unavoidable. The configuration of in situ bypass should be carefully tailored to each case, with consideration of variations in anatomy and pathology of the complex aneurysms.